The strategic planning process in quantity surveying firms during the declined period of 2001-2005 / Hasnanywati Hassan - Hassan, Hasnanywati (2010)
This study examines the strategic planning process of Malaysian quantity surveying firms. The method of providing strategic planning process is the main focus of this study. The strategic planning process which includes the efforts of strategic planning, degree of involvement in strategic planning and formality were analyzed. Strategic planning is the mechanism needed for organizations to stay competitive and enhance performance for the firms. The influence of the strategic planning process on quantity surveying firms' performance was determined. This study also highlights the influence of quantity surveying firms on the strategic planning process. The declined period in construction industry from year 2001 to 2005 has been determined as the research parameter. The research aims to 1) to establish the variables of quantity surveying firms 2) to establish the strategic planning process carried out by quantity surveying firms in terms of processes, degree of involvement and formality and 3) to establish the performance of quantity surveying firms. The influence of the strategic planning process on quantity surveying firms' performance was determined. This study also highlights the influence of quantity surveying firms on the strategic planning process. The declined period in construction industry from year 2001 to 2005 has been determined as the research parameter. The research aims to 1) to establish the variables of quantity surveying firms 2) to establish the strategic planning process carried out by quantity surveying firms in terms of processes, degree of involvement and formality and 3) to establish the performance of quantity surveying firms. The strategic planning process is examined using qualitative and quantitative data. A preliminary questionnaire survey was initially conducted, followed by semi-structured interviews with 15 top management of quantity surveying firms. A final postal questionnaire developed and then refined form the interview data was distributed to top management of quantity surveying firms. A total of 34 completed questionnaires form the data base for the quantitative analysis. The research concludes that Malaysian quantity surveying firms generally have mechanistic organization structure with Prospector orientation. The variables of quantity surveying firms influence the strategic planning process. The efforts of quantity surveying firms in the strategic planning process affect the quantity surveying firm performance. Most quantity surveying firms have semi formalized strategic plans. However, the degree of formalization of strategic plans does not affect the quantity surveying firms' performance.